Contrasting drivers of belowground nitrogen cycling in a montane grassland exposed to a multifactorial global change experiment with elevated CO2, warming, and drought. (10th January 2022) - Maxwell, Tania L.; Canarini, Alberto; Bogdanovic, Ivana; Böckle, Theresa; Martin, Victoria; Noll, Lisa; Prommer, Judith; Séneca, Joana; Simon, Eva; Piepho, Hans‐Peter; Herndl, Markus; Pötsch, Erich M.; et al.
Abstract: Depolymerization of high‐molecular weight organic nitrogen (N) represents the major bottleneck of soil N cycling and yet is poorly understood compared to the subsequent inorganic N processes. Given the importance of organic N cycling and the rise of global change, we investigated the responses of soil protein depolymerization and microbial amino acid consumption to increased temperature, elevated atmospheric CO2, and drought. The study was conducted in a global change facility in a managed montane grassland in Austria, where elevated CO2 (eCO2 ) and elevated temperature (eT) were stimulated for 4 years, and were combined with a drought event. Gross protein depolymerization and microbial amino acid consumption rates (alongside with gross organic N mineralization and nitrification) were measured using 15 N isotope pool dilution techniques. Whereas eCO2  showed no individual effect, eT had distinct effects which were modulated by season, with a negative effect of eT on soil organic N process rates in spring, neutral effects in summer, and positive effects in fall. We attribute this to a combination of changes in substrate availability and seasonal temperature changes. Drought led to a doubling of organic N process rates, which returned to rates found under ambient conditions within 3 months after rewetting. Notably, we observed a shift in the control of soil protein depolymerization, from plant substrate controls under continuous environmental change drivers (eT and eCO2 ) to controls via microbial turnover and soil organic N availability under the pulse disturbance (drought). To the best of our knowledge, this is the first study which analyzed the individual versus combined effects of multiple global change factors and of seasonality on soil organic N processes and thereby strongly contributes to our understanding of terrestrial N cycling in a future world. Abstract : Organic nitrogen (N) cycling is recognized as the major process controlling the overall soil N cycle, yet few studies investigated global change responses of soil organic N breakdown. We focused on the interactive effects of multiple global change drivers (warming × CO2  × drought) on soil protein depolymerization and microbial amino acid consumption. We found a shift in controls of these processes, from plant controls under warming and elevated CO2, to microbial turnover and soil organic N availability under push disturbances (drought). Seasonality modulated the effects of warming by changing the factors limiting soil organic N cycling.